PENGGUNAAN METODE 3M (MENIRU, MENGOLAH, MENGEMBANGKAN) DALAM PEMBELAJARAN MENULIS PUISI DI KELAS VIII - Khasanah, Mifta Ika; Azizah, Ririn Nurul (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2025)
This study aims to improve the poetry writing skills og eighth-grade students at Ar-Raudloh Junior High School through the 3M method (Imitate, Process, Develop). The background of this study stems from the fact that poetry writing instruction in schools remains theoretical, lacks exploration, and makes it difficult for students to express their ideas. The 3M method offers a step-by-step approach that allows students to understand, modify, and create poetry based on their own experiences. This study is a Classroom Action Research (CAR) conducted in two cycles with 24 female students as subjects. Data collection techniques include observation, interviews, written tests, and documentation. The results of the study showed an increase in the average poetry writing score from 75 (pre-action) to 80 (cycle I) and 83 (cycle II). This in increase was also accompanied by positive changes in student activity and confidence during the learning process. The quality of the poetry produced also improved in terms of diction, style, and expression of meaning. Students felt supported by the gradual and enjoyable learning process, while teachers assessed that this method facilitated guidance. This study concludes that the 3M method is effective in improving students’ poetry writing skills and has potential for broader application, including in the writing of other literary Works. ABSTRAKPenelitian ini bertujuan untuk meningkatkan keterampilan menulis puisi siswa kelas VIII E SMP Ar-Raudloh melalui metode 3M (Meniru, Mengolah, Mengembangkan). Latar belakang penelitian ini berawal dari kenyataan bahwa pembelajaran menulis puisi di sekolah masih bersifat teoritis, minim eksplorasi, dan membuat siswa kesulitan dalam mengeskpresikan ide. Metode 3M menawarkan pendekatan bertahap yang memberi ruang bagi siswa untuk memahami, memodifikasi, hingga menciptakan puisi berdasarkan pengalaman siswa itu sendiri. Penelitian ini merupakan Penelitian Tindakan Kelas (PTK) yang dilaksanakan dalam dua siklus dengan subjek 24 siswi. Teknik pengumpulan data mencakup observasi, wawancara, tes tertulis, dan dokumentasi. Hasil penelitian menunjukan peningkatan rata-rata nilai menulis puisi dari 75 (pra-tindakan), menjadi 80 (siklus I), dan 83 (siklus II). Peningkatan ini juga disertai perubahan posistif dalam keaktifan dan kepercayaan diri siswa selama proses pembelajaran. Kualitas puisi yang dihasilkan juga semakin baik dalam hal diksi, gaya bahasa, dan pengungkapan makna. Siswa merasa terbantu karena proses pembelajaran yang bertahap dan menyenangkan, sementara guru menilai metode ini mempermudah pendampingan. Kesimpulan dari penelitian ini adalah metode 3M efektif dalam meningkatkan keterampilan menulis puisi siswa dan memiliki prospek untuk diterapkan lebih luas, termasuk dalam penulisan karya sastra lainnya.